Comparison between Mesh Hernioplasty and Nylon Darn Repair in Inguinal Hernia Surgery; A Randomized Controlled Trail - Muhammad Umair Samee, Muhammad Furqan Sharif, Muhammad Abdullah Sheraz, Muhammad Abdullah Tahir, Fahad Ahmad Khan, Mirza Zeeshan Sikandar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: One of the procedures that is conducted the most frequently worldwide is inguinal hernia surgery. Several methods have been developed over time, but Lichtenstein has long dominated all others. This is said to lead to a less painful procedure and less suture tearing out, which lowers the likelihood of recurrence. Because to the paucity and high cost of commercial prosthetic mesh, conventional Bassini operations are still carried out at hospitals with minimal resources in developing nations. Because sutured material for darning repair is readily available, has a little amount of reactivity, and has acceptable recurrence rates, we compared it to Lichtenstein in this study. Inguinal hernia recurrence rates following non-mesh surgery range from 0.1 to 1%. Aim: This study is set out to compare darning with Lichtenstein technique of inguinal hernia repair in terms of frequency of post-operative complications, recovery and cost. Study Design: Prospective Randomized Control Trial Place and Duration of Study: This study was done in department of General surgery at Central Park Teaching Hospital, Lahore during a period of 4 months that span from October 2021 till January 2022. Methodology: Using a continuous simple random selection, 100 male patients between the ages of 20 and 80 who had been clinically diagnosed with an uncomplicated direct or indirect inguinal hernia were divided into two groups using a lottery system. This prospective randomised control trial included Group A, who underwent Darn Repair, and Group B, which underwent Open Mesh/Lichtenstein repair on the elective list (RCT). With follow-up at one week, six weeks, and one year, the primary end point compared the operating time, post-operative pain, analgesic requirement in the first 24 hours, length of hospital stay, time until return to work, surgical site infection, and hernia recurrence between patients who had Darning Repair (group A) and patients who had LMH (group B). Results: In group A, the average operation time and hospital stay following surgery were less. Early postoperative complication rates and the period before returning to work were comparable in both groups. The required length of analgesia was identical as were the pain scores at 24, 48, and 72 hours. Return to regular activity took an average of 5 weeks for each group, which was also comparable. During the 1-year assessment, the recurrence rates in the two groups were similar, at 4% after mesh repair and 4% following darn repair. Practical Implication: This will help in early and prompt management and repair of hernia even at smaller setups as nylon repair is as good as polypropylene mesh repair. Conclusion: Open inguinal hernia repair with a nylon darn was equal to polypropylene mesh with respect to early assessments of postoperative outcome and recurrence at 1 year. When compared to the Lichtenstein approach in individuals with inguinal hernias, the darn repair technique is straightforward, secure, affordable, and has a similar risk of recurrence. Keywords: Inguinal hernia, Lichtenstein Mesh Repair, Open Darn repair, recurrence rate.